Protocolo simplificado para a detecção molecular de Mycoplasma spp. em cultivos celulares - Michelon, Nathalia de Freitas (2025)
Contamination of cell cultures by Mycoplasma spp. is a major issue for laboratories that use cells, as it can affect research outcomes across various fields, interfere with diagnostics, and compromise the quality of biological products. The presence of Mycoplasma spp. in cultures is not easily detectable, and its detection requires laborious and time-consuming techniques, such as culturing, or complex and costly methods, often impractical for some diagnostic laboratories and especially for laboratories producing biological reagents. This study describes a simplified protocol for detecting Mycoplasma spp. in cell cultures, combining DNA extraction by thermal lysis with real-time PCR (qPCR) based on an intercalating dye (SYBR-Green). The qPCR was developed using high-coverage primers to amplify an 86-base pair fragment of the 16S rDNA gene, designed based on 109 Mycoplasma spp. sequences from GenBank, covering 13 species (dataset) and one sample identified in our laboratory. The reaction was optimized by adjusting primer concentrations, using the GoTaq® qPCR Master Mix kit (Promega). The standardization of thermal lysis considered parameters such as cell suspension volume, thermal exposure time, final resuspension volume in ultrapure water, and the need for subsequent centrifugation. The performance of the thermal lysis protocol was compared to phenol-chloroform extraction. After optimization, thermal extraction and qPCR were integrated into a continuous workflow, and its analytical sensitivity was evaluated. The combined protocol was applied to investigate Mycoplasma spp. in cultured cells with contamination status determined by conventional PCR after phenol-chloroform extraction. In silico analysis showed that the primers exhibited full annealing with dataset sequences of species frequently associated with culture contamination (M. arginini, M. hominis, M. orale, and M. hyorhinis). The thermal lysis protocol demonstrated comparable performance to phenol-chloroform extraction in qPCR, and the new workflow achieved a detection limit of 64 bacterial cells. Its application fully reproduced contamination results previously obtained by conventional PCR. In summary, the standardized protocol consists of thermal lysis at 99°C for 1 minute, followed by qPCR using high-coverage primers for the Mycoplasma spp. 16S rDNA gene. This method provides a simple, rapid, and cost-effective solution for monitoring Mycoplasma spp. contamination in cell cultures, serving as a valuable tool for laboratories conducting routine quality control of their biological reagents.